Secure Programming with C - Poston, Howard (EC-Council, 2020)
Secure coding with C is a top concern. Although the C programming language, which is commonly used in numerous applications and operating systems is popular, flexible, and versatile, it is inherently vulnerable to exploitation. Writing a secure code is crucial. Because there is no direct method to handle the exception (no in-built try and catch such as in another high-level language like C#) in the C language, it becomes the responsibility of the C developer to become extra vigilant while writing code. This course begins with a detailed explanation of the overall security of any C application. Further, it provides insights on how to write better C code, particularly a secure code that prevents pitfalls commonly encountered in the C language. This course shows you how to avoid vulnerabilities and security flaws resulting from the incorrect use of dynamic memory management functions. You will understand how to eliminate integer-related problems resulting from signed integer overflows, unsigned integer wrapping, and truncation errors.